Pellets Obtained from Iron Row Material in the Direct Reduction Processes - Africano-Higuera, Diana Carolina; Forero-Pinilla, Álvaro (Universidad Pedagógica y Tecnológica de Colombia, 2010)
Initially, representative samples of mineral fines, binders and coals, the reason for the study, were taken to characterize them. At the same time, the pelletizing disk of the laboratories of the UPTC School of Metallurgy was developed. Then we proceeded to make mixtures of mineral fines, coal and binder, in order to find the ideal proportions to obtain high-performance pellets, taking into account the kinetic and thermodynamic conditions of the process. The experimental design determined that the number of tests to be performed is 48, that is, 3 repetitions for each sample. Then, tests were carried out to study the reducibility of the pellets, evaluating the behavior of these with each of the binders once the reduction temperature had been reached. The pre-reduced obtained was analyzed by chemical and microscopic methods.